US drug policy landscape: insights and opportunities for improving the view - Kilmer, Beau (Occasional paper / RAND Drug Policy Research Center, 2012)
Discussions about reducing the harms associated with drug use and antidrug policies are often politicized, infused with questionable data, and unproductive. This paper provides a nonpartisan primer that should be of interest to those who are new to the field of drug policy, as well as those who have been working in the trenches. It begins with an overview of problems and policies related to illegal drugs in the United States, including the nonmedical use of prescription drugs. It then discusses the efficacy of U.S. drug policies and programs, including long-standing issues that deserve additional attention. Next, the paper lists the major funders of research and analysis in the area and describes their priorities. By highlighting the issues that receive most of the funding, this discussion identifies where gaps remain. Comparing these needs, old and new, to the current funding patterns suggests eight opportunities to improve understanding of drug problems and drug policies in the United States: (1) sponsor young scholars and strengthen the infrastructure of the field, (2) accelerate the diffusion of good ideas and reliable information to decision-makers, (3) replicate and evaluate cutting-edge programs in an expedited fashion, (4) support nonpartisan research on marijuana policy, (5) investigate ways to reduce drug-related violence in Mexico and Central America, (6) improve understanding of the markets for diverted pharmaceuticals, (7) help build and sustain comprehensive community prevention efforts, and (8) develop more sensible sentencing policies that reduce the excessive levels of incarceration for drug offenses and address the extreme racial disparities. The document offers some specific suggestions for researchers and potential research funders in each of the eight areas